INFORMATION AND COMMUNICATION TECHNOLOGIES AS A MEANS OF IMPROVING LANGUAGE TRAINING IN HIGH SCHOOL - Borysenko, V.; Gagina, N. (Continuing Professional Education: Theory and Practice, 2023)
In the article, the authors emphasize the need to continually update the content of higher education, to integrate the national education system into the world education community, to introduce a qualitatively new model of language training with the use of innovative learning technologies. The essential benefits of information and communication technologies in language training applying a student-centered approach are determined. It is stated that the incorporation of interdisciplinary integrated tasks and a wide range of electronic resources in the process of language learning provides the opportunities to identify and develop individual student capabilities, creates conditions for professional growth, self-actualization and self-determination by means of language, increases professionally oriented communication, shapes an individual perception of the world. The authors prove the effectiveness of computer-based language learning programmes where text information is combined with sound, color, graphics, pictures, animations, thus increasing students’ motivational level, improving perception and memorizing a large amount of information, stimulating their mental and verbal activity, enhancing the productivity of self learning, creating opportunities to develop students’ self-assessment skills. Some problems and difficulties associated with the application of computer technologies are identified in the article. The most common among them are insufficient preparedness of teachers to use ICT, their low awareness of the latest available software; poor technical support; slow production of teaching resources and materials. The authors outline the most important areas of improvement that will make it possible to use information and communication technologies effectively in language teaching.